2015
DOI: 10.1111/liv.12805
|View full text |Cite
|
Sign up to set email alerts
|

A high baseline HBV load and antiviral therapy affect the survival of patients with advanced HBV‐related HCC treated with sorafenib

Abstract: In patients with advanced HBV-related HCC treated with sorafenib, a high baseline HBV load was an adverse prognostic factor for survival. However, survival was significantly improved with the use of antiviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 34 publications
2
39
0
2
Order By: Relevance
“…The association between HBV viral load and mutation of nt1753 was still unclear. Moreover, many studies have demonstrated that a high viral load was an adverse prognostic factor for survival of HBV‐related HCC patients . Then the association of T1753C mutation and HBV‐related HCC patients’ survival were still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The association between HBV viral load and mutation of nt1753 was still unclear. Moreover, many studies have demonstrated that a high viral load was an adverse prognostic factor for survival of HBV‐related HCC patients . Then the association of T1753C mutation and HBV‐related HCC patients’ survival were still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, sorafenib has an additional inhibitory effect on multiple steps of HCV replication [ 135 , 136 ]. In HBV-related HCC treated with sorafenib, high HBV load was associated with poor prognosis unless an anti-viral therapy was added to the therapy [ 137 ].…”
Section: Therapeutic Applications Of Targeting Vegf In Viral Diseamentioning
confidence: 99%
“…Likewise, anti‐viral therapy after radiofrequency ablation is associated with decreased HCC recurrence . The data on anti‐viral therapy in patients treated with palliative therapy, including transarterial chemoembolisation (TACE) and sorafenib are more limited, but in the case of TACE, a randomised controlled trial demonstrated that anti‐viral therapy increases survival …”
Section: Introductionmentioning
confidence: 99%